The stereodynamics of 1,2-dipropyldiaziridines - Trapp, Oliver; Sahraoui, Laila; Hofstadt, Werner; Könen, Werner (Chirality, 2010)
N-alkylated trans-diaziridines are an intriguing class of compounds with two stereogenic nitrogen atoms which easily interconvert. In the course of our investigations of the nature of the interconversion process via nitrogen inversion or electrocyclic ring opening ring closure, we synthesized and characterized the three constitutionally isomeric diaziridines 1,2-di-n-propyldiaziridine 1, 1-isopropyl-2-n-propyldiaziridine 2, and 1,2-diisopropyldiaziridine 3 to study the influence of the substituents on the interconversion barriers. Enantiomer separation was achieved by enantioselective gas chromatography on the chiral stationary phase Chirasil-β-Dex with high separation factors α (1-isopropyl-2-n-propyldiaziridine: 1.18; 1, 2-diisopropyldiaziridine: 1.24; 100°C 50 kPa He) for the isopropyl substituted diaziridines. These compounds showed pronounced plateau formation between 100 and 150°C, and peak coalescence at elevated temperatures. The enantiomerization barriers ΔG‡ and activation parameters ΔH‡ and ΔS‡ were determined by enantioselective dynamic gas chromatography (DGC) and direct evaluation of the elution profiles using the unified equation implemented in the software DCXplorer. Interestingly, 1-isopropyl-2-n-propyldiaziridine and 1,2-diisopropyldiaziridine exhibit similar high interconversion barriers ΔG‡ (100°C) of 128.3 ± 0.4 kJ mol−1 and 129.8 ± 0.4 kJ mol−1, respectively, which indicates that two sterically demanding substituents do not substantially increase the barrier as expected for a distinct nitrogen inversion process. Chirality, 2010. © 2009 Wiley-Liss, Inc.